Readiness Center Learning with Audio-Visual Media to Enhance the Competence of Early Childhood Education Teachers in Ringinarum Kendal (Universitas Negeri Semarang, 2019)
This study aims to develop learning towards improving the competence of Early Childhood Education teachers. The object of this research was the readiness center learning model using audio-visual media. The result of development was a prototype model of early childhood education in the form of a textbook, readiness center learning, and audio-visual media. The audio-visual media in the form of a Compact Disc (CD) comprising Universe Theme for Natural Phenomena Subtheme (Flood, Earthquake, Eruption, Rain, Rainbow, Morning Day Night). The use of CD requires teachers to be able to operate computers, LCD, and projector. Therefore, teachers can enhance their competence in IT mastery. Readiness center model using audio-visual effectively increases the competence of early childhood education teachers in managing quality learning and developing achievements on cognitive and psychomotor aspects.